Turning the Page on Pen-and-Paper Questionnaires: Combining Ecological Momentary Assessment and Computer Adaptive Testing to Transform Psychological Assessment in the 21st Century - Gibbons, Chris J. (Frontiers in Psychology, 2017)
Abstract The current paper describes new opportunities for patient-centred assessment methods which have come about by the increased adoption of affordable smart technologies in biopsychosocial research and medical care. In this paper, we review modern assessment methods including item response theory (IRT), computer adaptive testing (CAT), and ecological momentary assessment (EMA) and explain how these methods may be combined to improve psychological assessment. We demonstrate both how a ‘naïve’ selection of a small group of items in an EMA can lead to unacceptably unreliable assessments and how IRT can provide detailed information on the individual information that each item gives thus allowing short form assessments to be selected with acceptable reliability. The combination of CAT and IRT can ensures assessments are precise, efficient, and well targeted to the individual; allowing EMAs to be both brief and accurate.